EMOTION-LADEN TEXTS AND WORDS - Driver, Meagan (Studies in second language acquisition, 2022)
This study takes a mixed-methods approach to explore the influence of emotion-laden (positive vs. negative vs. neutral) texts and words on vocabulary learning for Spanish heritage and foreign language learners. Participants (N = 121) were tasked with learning emotion-laden pseudowords embedded in three emotion-laden texts centered around themes of bilingualism, immigration, and identity. Form recognition, translation, and multiple-choice tests were designed to measure vocabulary recall and retention. Results from a mixed-effects modeling analysis showed that the neutral and negative emotion-laden texts predicted better vocabulary learning outcomes than the positive text for both HLLs and FLLs and that neutral words were learned best by all learners. Qualitative findings from open-ended questionnaires suggest emotional arousal as another influential affective factor in vocabulary learning for learners of diverse sociolinguistic backgrounds. Directions for future emotions research in SLA and pedagogical implications of socially relevant, emotion-laden material for vocabulary learning are discussed.